If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2y = 29 Solving x + 2y = 29 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. x + 2y + -2y = 29 + -2y Combine like terms: 2y + -2y = 0 x + 0 = 29 + -2y x = 29 + -2y Simplifying x = 29 + -2y
| -3x+8=18+4x | | x+2x=62 | | x-3(x-4)+2=14-3(5x+6) | | 3*n-8=2*n+15 | | 4(6x+3x)=12 | | 60k+60k=50k+100 | | x+x+2=62 | | -9+2.5y-.7y+1+6.4y= | | 2.4x=4x-88 | | X^2+5x=46 | | xy-d=mfory | | -18+9x=63 | | 2(x+4)+3(-x)=2(-x) | | -x+1=3x+21 | | 6X-1Y=18 | | 2(4c-1)=8c-2 | | x-2x-3=-x+9 | | 2s+8=22 | | 3(5x-4)-8x=7x-12 | | -7x+14=49-2x | | 10y+8x=314 | | 5y-3=2y-6 | | 4v-12-7v=6-2v | | 2x+5yx+y=3 | | 25=k+23 | | -5u+6=12u+62 | | 2x+10=-40+3x | | 22-6x=2(3x-11) | | 10y^2-60y=0 | | (x-10)+x=90 | | 3z+2=-10-4z+7z | | 5x-29=x+7 |